Evidences for centennial dry periods at 3300 and 2800 cal. yr BP from micro-facies analyses of the Dead Sea sediments. (August 2015) - Neugebauer, Ina; Brauer, Achim; Schwab, Markus J; Dulski, Peter; Frank, Ute; Hadzhiivanova, Elitsa; Kitagawa, Hiroyuki; Litt, Thomas; Schiebel, Vera; Taha, Nimer; Waldmann, Nicolas D; ,
Laminated lake sediments from the Dead Sea basin provide high-resolution records of climatic variability in the eastern Mediterranean region, which is especially sensitive to changing climatic conditions. In this study, we aim on detailed reconstruction of climatic fluctuations and related changes in the frequency of flood and dust deposition events at ca. 3300 and especially at 2800 cal. yr BP from high-resolution sediment records of the Dead Sea basin. A ca. 4-m-thick, mostly varved sediment section from the western margin of the Dead Sea (DSEn – Ein Gedi profile) was analysed and correlated to the new International Continental Scientific Drilling Program (ICDP) Dead Sea Deep Drilling Project core 5017-1 from the deep basin. To detect even single event layers, we applied a multi-proxy approach of high-resolution microscopic thin section analyses, micro-X-ray fluorescence (µ-XRF) element scanning and magnetic susceptibility measurements, supported by grain size data and palynological analyses. Based on radiocarbon and varve dating, two pronounced dry periods were detected at 3500–3300 and 3000–2400 cal. yr BP which are differently expressed in the sediment records. In the shallow-water core (DSEn), the older dry period is characterised by a thick sand deposit, whereas the sedimentological change at 2800 cal. yr BP is less pronounced and characterised mainly by an enhanced frequency of coarse detrital layers interpreted as erosion events. In the 5017-1 deep-basin core, both dry periods are depicted by halite deposits. The onset of the younger dry period coincides with the Homeric Grand Solar Minimum at ca. 2800 cal. yr BP. Our results suggest that during this period, the Dead Sea region experienced an overall dry climate, superimposed by an increased occurrence of flash floods caused by a change in synoptic weather patterns.